Volatile composition changes in lemon during fruit maturation by HS‐SPME‐GC‐MS. (8th January 2022) - Li, Chunxiu; Li, Xunlan; Liang, Guolu; Xiang, Suqiong; Han, Guohui
Abstract: BACKGROUND: Volatiles are determinants of fruit aroma and flavor characteristics and also provide valuable information for lemon as ingredient for the food and drinks industry. Volatiles in 'Eureka' lemon and 'Xiangshui' lemon pulps from 130 to 186 days after flowering were enriched by headspace–solid‐phase microextraction (HS‐SPME), and analyzed by gas chromatography–mass spectrometry (GC‐MS). RESULTS: Seventy‐seven volatiles of two lemon cultivars at the different ripening stages were identified and divided into six categories. Varieties and ripening stages had significant effects on individual volatiles in each category. The proportion of monoterpenes was found to be higher in 'Eureka' lemon, while 'Xiangshui' lemon had a higher proportion of sesquiterpenes, aldehydes and alcohols. The proportion of monoterpene fluctuation decreased during fruit ripening, while fluctuation of sesquiterpenes, alcohols, aldehydes and esters increased. Among the hydrocarbons, monoterpenes decreased their relative abundance from 91.67% to 81.04% in 'Eureka' lemon, and from 83.01% to 60.04% in 'Xiangshui' lemon; conversely, sesquiterpenes increased from 0.73% to 2.89% in 'Eureka' lemon, and from 3.21% to 8.48% in 'Xiangshui' lemon. Among the oxygenated volatiles, the proportions of alcohols, aldehydes and esters were higher at 186 days after flowering in both two cultivars. CONCLUSION: The volatile organic compounds during fruit ripening of lemon varieties with different resistance were elucidated. The proportion of oxygenated volatiles increased during fruit ripening, and disease‐resistant varieties had a higher proportion. These results provided important theoretical support for the utilization of lemon fruits and the innovation of disease‐resistant germplasm resources. © 2021 Society of Chemical Industry.